2022
DOI: 10.3389/fbioe.2022.876675
|View full text |Cite
|
Sign up to set email alerts
|

Standardization of the FAO/IAEA Flight Test for Quality Control of Sterile Mosquitoes

Abstract: Successful implementation of the sterile insect technique (SIT) against Aedes aegypti and Aedes albopictus relies on maintaining a consistent release of high-quality sterile males. Affordable, rapid, practical quality control tools based on the male’s flight ability (ability to escape from a flight device) may contribute to meeting this requirement. Therefore, this study aims to standardize the use of the original FAO/IAEA rapid quality control flight test device (FTD) (version 1.0), while improving handling c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 54 publications
1
16
0
Order By: Relevance
“…From all evaluated parameters for chilling, we found that the escape rate (provided by the flight ability test) was more sensitive than survival and immediate mortality to detect a potential impact after 60 min at 4 °C. The escape rate was pointed out as an excellent quality control parameter since it is sensitive to distinguish differences among species, ages, and stress levels (i.e., irradiation, chilling, compaction), which reflects directly the male quality [ 39 , 58 ]. During an operational program is essential to have quicker tools to provide data to help managers make timely decisions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From all evaluated parameters for chilling, we found that the escape rate (provided by the flight ability test) was more sensitive than survival and immediate mortality to detect a potential impact after 60 min at 4 °C. The escape rate was pointed out as an excellent quality control parameter since it is sensitive to distinguish differences among species, ages, and stress levels (i.e., irradiation, chilling, compaction), which reflects directly the male quality [ 39 , 58 ]. During an operational program is essential to have quicker tools to provide data to help managers make timely decisions.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, compaction did not affect the full insemination rate; this result contrasts with the study of Culbert et al (2018) [ 41 ]. We also have to consider the role of different strains, species, insect age, and methodological performance in this response, as was recently pointed out by Maïga et al (2022) [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…To avoid prolonging the male production duration in an SIT facility, no more than 2 fractionated doses were considered for this study. Nor were recovery periods of more than 2 days considered between exposures, as it has been recommended to release the sterile males at around day 4 or 5 at the peak of their flight and mating activity, after which the flight ability begins to decline [ 29 ]. One and 2 days were selected as intervals also to ensure that there was sufficient time for the males to recover not only from the effects of the first irradiation, but also from the stress of handling before and during exposures, as it has been shown that, for example, flight ability is restored when males are given 1–2 days of rest post-exposure [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…There was no difference observed in flight ability between males subjected to acute or fractioned doses. All treatment groups performed equally as compared to non-irradiated control groups, except treatment group F. This result suggests that subjection to one high dose, or the double handling, or only having one recovery day is tolerable in terms of flight ability; however, when all three factors are combined, this reduces the overall male quality, which is reflected by the reduced escape rates [ 29 ]. Although not statistically significant, the trend was that the double handled males all had the lowest recorded escape rates (C–F), when compared to the low scores of the males handled only once (A and B), suggesting that stress from handling can be more detrimental than irradiation itself [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation